Basement Configuration Of Labuan Basin, Pandeglang, Based On Gravity Data - Lina Handayani; Dadan Dani Wardhana (Jurnal Geologi dan Sumberdaya Mineral, 2020)
Pandeglang is located on the coast of the Sunda Strait, which is tectonically active as the source of geological hazards. Basement configuration mapping is required for further understanding in geological characteristic of the land. Gravity method is one of the geophysical techniques that can be applied for the regional subsurface characterization. Gravity measurements were completed in the Pandeglang area, from Tanjung Lesung to Labuan coastline and all passable roads in Pandeglang Regency. The Bouguer anomaly obtained has indicated a steady decreasing anomaly from south-southwest to north-northeast area. The result of residual anomalies analysis and basement depth estimation presented a deep basin in the northeast most of the study area (Labuan â€“ Picung), which indicates a thick sediment layer in this area.Keywords: gravity anomaly, residual anomaly, basin, basement, Labuan, Pandeglang.Â